2019
DOI: 10.1037/bar0000114
|View full text |Cite
|
Sign up to set email alerts
|

Impacting pediatric primary care: Opportunities and challenges for behavioral research in a shifting healthcare landscape.

Abstract: Behavior analysts have long recognized the potential of a partnership with pediatric medicine as an opportunity to expand the influence of behavior analysis and positively impact population health. Despite significant achievements in this domain, the impact of behavioral science on the daily practice of pediatrics has been limited. In this commentary, the authors argue that the current health care and research environments are ripe for a renewed focus on behavioral modification in pediatric primary care, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 143 publications
(176 reference statements)
0
3
0
Order By: Relevance
“…Both groups also identified a need for institutional policies that can help improve service delivery for patients with ASD. Importantly, even though the behavioral literature has widely examined behavioral interventions for increasing compliance with medical procedures (e.g., Kupzyk & Allen, 2019 ; Riley & Freeman, 2019 ), neither the medical trainees nor the physicians in this study demonstrated a strong understanding of behavioral function, as evidenced by attributing severe behavior to internal factors such as “maintaining inner peace.”…”
Section: Discussionmentioning
confidence: 90%
“…Both groups also identified a need for institutional policies that can help improve service delivery for patients with ASD. Importantly, even though the behavioral literature has widely examined behavioral interventions for increasing compliance with medical procedures (e.g., Kupzyk & Allen, 2019 ; Riley & Freeman, 2019 ), neither the medical trainees nor the physicians in this study demonstrated a strong understanding of behavioral function, as evidenced by attributing severe behavior to internal factors such as “maintaining inner peace.”…”
Section: Discussionmentioning
confidence: 90%
“…The collection of articles described above report on varied IPC models utilizing a range of qualitative and quantitative methodologies drawn from QI, implementation science, and health services research. Just as IPC clinicians must flexibly adapt interventions that were originally developed for specialty behavioral health settings, IPC researches must embrace a slew of scientific methods to adequately address the questions facing our field (Riley & Freeman, 2019). We need a workforce of clinicians and researchers with specialized knowledge and skills in implementation and evaluation that match the demands of the IPC setting.…”
Section: Training and Workforce Developmentmentioning
confidence: 99%
“…These authors bring these issues to bear and remind us that historically, behavior analysts have not always paid enough attention to building rapport with patients and families. Riley and Freeman (2019) explore why the plethora of evidence-based treatments that have been developed to effectively treat child BH problems has not made their way into the primary care pediatric setting to date. The authors make the case that the demand for basic parent training techniques such as time-in and time-out remains robust, and despite all of the resources dedicated to addressing basic behavior problems in children, the problems are persisting and the demand remains strong.…”
mentioning
confidence: 99%